Effects of Hygrothermal Environment in Cooling Towers on the Chemical Composition of Bamboo Grid Packing - Chen, Li-Sheng; Fei, Ben-Hua; Ma, Xin-Xin; Lu, Ji-Ping; Fang, Chang-Hua (Forests, 2019)
Bamboo grid packing (BGP) is a new kind of cooling packing, used in some Chinese hyperbolic cooling towers, which has excellent potential to complement or replace cooling packing made of polyvinyl chloride (PVC), cement, and glass fiber-reinforced plastic. For bamboo applications, mechanical properties and service life are matters of concern; this is strongly associated with bamboo’s chemical composition and mass loss. To better understand the mechanics of mechanical property deterioration and service life reduction, this study investigated the effects of hygrothermal environments in cooling towers on the chemical and elemental composition, mass loss, Fourier-transform infrared (FTIR) spectrum, and color changes of BGP. The results showed that BGP that had been in service for nine years in cooling towers exhibited major decreases in content of hemicellulose and benzene-ethanol extractives, as well as a significant increases in the content of α-cellulose and lignin. Exposure to the hygrothermal environment led to a decrease of oxygen content and around 8% mass loss, as well as an increase in carbon content compared to control samples. The hot water flow in cooling towers not only hydrolyzed hemicellulose, but also degraded some functional groups in cellulose and lignin. The lightness (L*) and chromaticity (a* and b*) parameters of the used BGP all decreased, except for the a* value of the outer skin. The total color change (ΔE*) of the inner skin of used BGP exceeded that of the outer skin.